Teores nutricionais em folhas e frutos de figueira, submetida a épocas de poda e irrigação - Leonel, Sarita [UNESP]; Tecchio, Marco Antonio [UNESP] (Universidade Estadual de Londrina (UEL), 2009)
The present study aimed to evaluating the nutritional content in leaves and fruits of the fig tree 'Roxo de Valinhos', pruned at different periods corresponding to the months of July, August, September and October in the years of 2004 and 2005, with and without the use of irrigation, in the county of Botucatu, São Paulo State, Brazil. To achieve this objective, the adopted experimental design was in blocks with subdivided plots and 5 replications, in which plots corresponded to treatments with and without irrigation and subplots included prunings done in the above-mentioned four months. The levels of N, P, K, Ca, Mg, S, B, Cu, Mn and Zn in leaves and fruits were evaluated in the two crop cycles. The results indicated no significant differences among macro and micronutrient levels in the leaves subjected to treatments with and without irrigation in the cycle 2004/05, except for cupper which showed higher level with the treatment including irrigation (6 mg kg(-1)). In the fruits, there was no difference, except for Zn, which also showed the highest levels (28 mg kg(-1)) with irrigation. In the crop cycle 2005/06, there were differences for N (40 g kg(-1)) and K (20 g kg(-1)) in the leaves, where the highest levels were observed with the treatment including irrigation. In the fruits, N had significant difference and its highest level was observed without irrigation (21 g kg(-1)). In relation to the pruning periods, significant differences were observed for Ca, Fe and Zn content in the leaves and Ca, K, Mg, S and Zn content in the fruits in the crop cycle 2004/05. In the cycle 2005/06, there were not differences among the levels of the evaluated nutrients in the leaves, and in the fruits there was difference for N, Ca and Cu.
The nutritional levels in leaves and fruits of fig trees as a function of pruning time and irrigation
Keywords: Ficus carica L; nutrition